HUBUNGAN KUAT TEKAN DAN KUAT LENTUR BETON DENGAN MUTU Fc’ 25 MEGAPASCAL (MPa) - Khairu Imanda Pratama; Pio Ranap Tua Naibaho; Sempurna Bangun (Universitas Trisakti, 2023)
Along with the development of the times in the construction sector, there are so many new innovations in the infrastructure sector. The use of concrete construction is in demand because concrete has beneficial properties such as fire resistance, durability, high compressive strength and in practice it is easy to shape into the desired shape. Concrete material consists of a mixture of cement, coarse aggregate, fine aggregate, water and sometimes with innovative additives. The research method used in this research is experimental, by making sample test objects in the laboratory using two different specimens but with the same concrete quality, namely fc'25 MPa. Based on the results of the values ​​on the flexural and compressive test specimens in the laboratory, it has been found that an unsuitable relationship between flexural strength (fs) and compressive strength (fc ') is in accordance with SNI 2847: 2013. The formula (fr = 0.62) applies to the 28-day-old concrete test.